The inhibitory effect of Cordia myxa (Linn)Extractes progeny against the isolated fungi from patients with pulmonary diseases in AL-Diwaniya City - Majed kadem Al-shibly; Farqad Abdul elah Al-janahi (Al-Qadisiyah Journal of Pure Science, 2017)
The present study involved collecting 240 sample of sputum from patients with pulmonary infections who visited the pulmonary disease clinic in Al-Diwaniya city from October 2010 to april 2011 from isolated and diagnostic fungi in itand test the effect of Cordia myxa(L.) progeny alcoholic and equeous extracts from it,the isolated fungi involved: penicillium spp, Candida albicans Ùˆ Aspergillus niger , A.nidulan , A.flavu, A.terrus,Mucor, Pithomyces chartarum , Coccidioides immitis and Blastomyces dermatitidis with number of isolate and the number of percenant of isolations wer :82- 32.03%,70-27.45% ,20 -7.81%,3-1.17% ,10-3.906%, 2-0.78%, 1 - 0.39,% -2 0.78% and 2 - 0.78.% respwctively .Than the effects of antifungal from the isolated fungi show that the ketoconazole the hier inhibition at Cconcenteration 100% were respectively (2.65,2.9,2.9,4.25,2.5,2.9,3,3,3,2.5) from Aspergillus flavus Ùˆ A.nidulanes Ùˆ A.nigerÙˆ A.terreus Ùˆ Blastomyces dermatitidisÙˆCandida albicansÙˆ Coccidioides immitis Ùˆ Penicillium sppÙˆ Mucor while at 50 % cocenteration ( 2.5 Ùˆ 2 Ùˆ 2 Ùˆ 2.5 Ùˆ 2.1 Ùˆ 2 Ùˆ 2.5 Ùˆ 2.5 Ùˆ 2.8 Ùˆ 1 ( respectively but Nystatin have lower inhibition between the antifungal.The effect of Cordia myxa(L.) progeny alcoholic and equeous extracts from isolated fungi semmes clear at al coholic extract than the equeous therfor show the rang of radial inhibition zone : (4,3,3,1.5,1.2,1)cm from fungi Aspergillus flavus , Blastomyces dermatitidis,Pithomyces chartarum ,A.niger ,A.terreus, Coccidioides immitis respectively,while it has no effect on other fungi that :Penicillium spp , Candida albicans, A.nidulanes, Mucor.